Hb H disease associated with compound heterozygosity for --SEA deletion and a novel alpha globin chain variant (HBA2:c.175C>A) on the distal histidine in a Chinese family - Manna Sun; Jiwu Lou; Wang Xinghe; Ying Zhao; Yunshi Dai; Shuangai Liu; Tizhen Yan (Hematology)
Objectives: In clinical practice, the majority of α-thalassaemia cases arise from deletions of the α-globin genes. However, a subset of cases is attributed to rare haemoglobin variants, which can manifest with borderline or normal screening results, potentially leading to missed diagnoses in clinical practice.Methods: Blood samples were collected from family members and underwent haematological, DNA and RNA analysis.Results: The five-month-old proband presented a haematological phenotype consistent with Hb H disease. The mother’s haematology profile was consistent with an α-thalassaemia carrier, while the father exhibited a borderline reduction in MCV and MCH. MALDI-TOF identified an abnormal α-chain in the proband. DNA analysis revealed a novel α-globin variant (HBA2:c.175C>A, α58His>Asn, Hb DG-Nancheng) affecting the distal histidine in the family. The father and the mother had α-genotype of --SEA/αα and αDG-Nanchengα/αα, respectively; while the proband inherited both mutant alleles (--SEA/αDG-Nanchengα). Sequencing of cDNA from HBA2 gene identified an equal ratio of normal and mutant alleles.Conclusion: This rare case highlighted the importance of identifying rare haemoglobin variant during prenatal screening. The clinical and genetic data provides useful information on the pathogenicity of this variant and further insight into the role of distal histidine residue of α-globin.